Factors associated with mothers' knowledge of children with congenital heart disease in Bangkok, Thailand - Malatree Khouenkoup; Arunrat Srichantaranit; Wanida Sanasuttipun (Journal of Health Research, 2022)
Purpose – This study aimed to determine mothers' knowledge of children with congenital heart disease (CHD) and to examine the relationship between types of CHD, the duration of treatments, the perception of the severity of illness and the mothers' knowledge. Design/methodology/approach – A correlation study was conducted among 84 mothers of children (from infancy to six years old) with CHD who had attended pediatric cardiology clinics and pediatric units in three tertiary hospitals in Bangkok, Thailand. The two questionnaires aimed to evaluate the mothers' knowledge and perceptions of the severity of illness. Descriptive statistics, Spearman's rank-order correlation and Fisher's exact test were used to analyze the data. Findings – Knowledge levels of mothers of children with CHD were at a high level with a mean score of 34.79 (SD = 8.23), but the knowledge domain of preventing complications was at a low level with a mean score of 14.95 (SD = 5.28). The types of CHD and the perceptions of illness were not correlated with the mothers' knowledge, but the duration of treatments was significantly correlated (r = 0.271, p < 0.05). Originality/value – Healthcare professionals, especially nurses, should emphasize proper health education on complication prevention and the duration of treatments for children. Moreover, mothers should be supported to nurture children with CHD to reduce possible complications and prepare for cardiac surgery where needed.